Pengaruh Penerapan Sweeping Bagasi Penumpang Maskapai Citilink terhadap Optimalisasi Kinerja Petugas Boarding Gate PT Gapura Angkasa Yogyakarta International Airport - Fauziah, Syifa; Syahputri, Khofifah Indah (Jurnal Manajemen Dirgantara, 2025)
Aviation, as an important mode of transportation, demands strict safety standards, one of which is through the implementation of baggage sweeping. Citilink at Yogyakarta International Airport has implemented baggage sweeping to improve safety and operational efficiency. This process involves the vital role of ground handling officers in ensuring flight security. However, officers face obstacles in the form of a lack of understanding and passenger resistance to the baggage sweeping policy. These obstacles have the potential to affect officer performance and passenger satisfaction. Therefore, proper baggage sweeping management is necessary to maintain security without reducing service quality. This study aims to analyze the effect of baggage sweeping implementation on optimizing the performance of departure gate officers. The research method used is quantitative with data collection through questionnaires. The study respondents included all 45 departure gate officers of PT Gapura Angkasa at Yogyakarta International Airport. Data analysis was conducted using SEM PLS 4.0 through validity, reliability, R-square, and hypothesis testing. The results showed that the implementation of baggage sweeping had a positive and significant effect on officer performance with a coefficient of 0.821 and an R-square of 0.673. Strict baggage inspection procedures are the most dominant factor, while reducing baggage damage and punctuality of boarding require further attention.